Several Narrative Strategies in Yiddish and Czech Stories - Holý, Jiří (Poznańskie Studia Slawistyczne, 2023)
This article deals with six short stories written in Yiddish and Czech analyzing their narrative strategies. In The German by Sholem Aleichem the limited first-person perspective of the story makes it impossible to look into the inner world of the German. Similar characters are presented in Aleichem’s Hard Luck and Elijah the Prophet. At the end of Hard Luck a dialogue breaks the limited perspective. The main character of Isaac Leybush Peretz’s The Shtrayml seems to be a type of naive narrator; in fact, in the last part of the story, he expresses the author’s irony and social criticism. The German by Aleichem probably inspired The Miracle with Julča by Czech author Ivan Olbracht. Here, however, the protagonist’s perspective is sometimes extended by the author’s perspective. In Ladislav Grosman’s The Bride the contrast between the characters’ and the readers’ expectations is presented by the significant change of the narrator’s point of view. The peripheral narrator concentrated on private life becomes the author’s narrator who knows the future.